Weaving memories: the creation and trajectory of the project “The city for all: perception, belonging, and preservation of the cultural heritage as a way of constituting the senses of collectivity in Bocaina city” - Assumpção, Ana Laura; Bevilaqua, Bruna Cristina; Castral, Paulo César (National Journal of City Management, 2022)
The project "The city for all: perception, belonging, and preservation of the cultural heritage as a way of constituting the senses of collectivity in Bocaina city”, created in 2020, is an initiative of the Research Center for Language Studies in Architecture and City of the Institute of Architecture and Urbanism of the University of São Paulo, in São Carlos. Supported by the citizen science methodology, it aims at sharing scientific actions between university and city and creating a space for dialogue with the population towards a collective construction of scientific and empirical knowledge about Bocaina and subsidies for the development of public policies for the city focused on Cultural Heritage. This article describes the project and its trajectory to date for encouraging the design of projects in other contexts as a way to establish links, stimulate a sense of belonging, and above all, keep the local collective memory alive, thinking, in other words, in the broader sense of the [univer]city" concept.